Sejarah Gereja Katolik Paroki Santa Filomenamena Tahun 1994-2023 Desa Desa Oepuah Selatan Kecamatan Biboki Moenleu Kabupaten Timor Tengah Utara - nese, maria selfiana; ande, Andreas; Ndoen, Fransina (FLORESIENSIS, 2022)
The research in this thesis aims to find out the history of the Santa Filomena Mena Catholic Church in 1994-2023 in South Oepuah Village, Biboki Moenleu District, North Central Timor Regency. Research purposes; (1) to find out the history of the founding of the Santa Filomena Mena Catholic Church, (2) to find out the development of the Santa Filomena Mena Catholic Church, (3) to find out the reasons why people still practice traditional beliefs to this day, (4) to find out the process of religious incubation Catholicism and local culture. This type of research is historical research. Determination of informants is done by Snowball sampling, the data sources used are primary data sources and secondary data sources. Data collection techniques in this study were interviews, observation, and document studies. Data analysis techniques in this study are heuristics, criticism, interpretation, and historiography. The results of this study are: (1) The history of the founding of the Catholic Church of Santa Filomena Mena, at first it was still part of the Ponu Mother of God Parish, however, judging from the distance from the main parish it was very far, Fr Paulus Gootte, SVD built 3 ( three) Chapel. The decision as Mena Parish Candidate refers to the Decree of the Bishop of Atambua Mrg. Antonius Pain Ratu, SVD with No. 27 dated 19 January 1994. (2) Development of the Santa Filomena Mena Catholic Church in 1994-2023. (a) Church House, (b) people (c) Religious Organizations, (d) Activities. (3) The community in general has embraced the Catholic Religion, but the community still continues to practice traditional beliefs, namely Animism and Dynamism to this day. However, for Atoen Meto, culture and tradition cannot be lost or extinct, one of which is traditional belief, namely Anismism and dynamism, which are still practiced today. (4) The process of inculturation of Catholicism and local culture in the people of South Oepuah Village.